2018
DOI: 10.3390/brainsci8110194
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease and Metal Storage Disorders: A Systematic Review

Abstract: Metal storage disorders (MSDs) are a set of rare inherited conditions with variable clinical pictures including neurological dysfunction. The objective of this study was, through a systematic review, to identify the prevalence of Parkinsonism in patients with MSDs in order to uncover novel pathways implemented in Parkinson’s disease. Human studies describing patients of any age with an MSD diagnosis were analysed. Foreign language publications as well as animal and cellular studies were excluded. Searches were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…While not pathologically proven, the CT hyperattenuation in this case is most consistent with calcification, as previously reported in common clinical practice and in the literature [3,10]. It is difficult to find CT-pathologic correlation in the literature for HH and brain iron accumulation, which may in part be because some or most brain iron accumulation do not demonstrate calcification [12,16].…”
Section: Discussionsupporting
confidence: 70%
“…While not pathologically proven, the CT hyperattenuation in this case is most consistent with calcification, as previously reported in common clinical practice and in the literature [3,10]. It is difficult to find CT-pathologic correlation in the literature for HH and brain iron accumulation, which may in part be because some or most brain iron accumulation do not demonstrate calcification [12,16].…”
Section: Discussionsupporting
confidence: 70%
“…But yet the complex multifactorial mechanisms of parkinsonism are not fully understood so far. It has been proposed previously that Manganese can cause severe neurological damage [1]. Parkinsonism is defined as the presence of bradykinesia, rest tremor and rigidity.…”
Section: Introductionmentioning
confidence: 99%
“…Atypical syndromes can involve psychiatric disturbances, as well as difficulties with gaze, autonomic function, and sensation. A 2018 systematic review of 50 papers found seven papers describing both typical and atypical Parkinsonian symptoms associated with HH [ 12 ]. These studies were also all associated with Parkinsonian symptoms that were unresponsive to treatment with traditional pharmacologic therapy such as levodopa [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2018 systematic review of 50 papers found seven papers describing both typical and atypical Parkinsonian symptoms associated with HH [ 12 ]. These studies were also all associated with Parkinsonian symptoms that were unresponsive to treatment with traditional pharmacologic therapy such as levodopa [ 12 ]. This pattern was corroborated in our patient, where dopamine agonists and levodopa-carbidopa did not alleviate his neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%